Peranan Penyidik Bea Dan Cukai Dalam Pemberantasan Tindak Pidana Penyelundupan Pakaian Bekas: Studi Kasus Di Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madyan Atambua - Imelda Rosari Bau; Deddy R.C Manafe; Rosalind Angel Fanggi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Smuggling of used clothes is a criminal act that is still a serious problem in Indonesia.This is certainly a concern from various parties, especially Customs and Excise as an agency that has duties and responsibilities in the field of Customs. Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 gives authority for Customs and Excise to carry out their roles in accordance with the scope of duties and functions carried out. However, in practice in the field, cases of smuggling of used clothes continue to be found, one of which is in the Atambua City area This research uses an empirical juridical research method, which is a study that directly examines the phenomenon of smuggling used clothes that occurs in the field, as well as the role of Customs and Excise investigators and the obstacles of Customs and Excise investigators in eradicating the smuggling of used clothes by conducting an interview with the Head of the Atambua Customs and Excise Office, Head of the Atambua Customs and Excise Enforcement and Investigation Section, Atambua Customs and Excise Investigator Members and the public who are consumers and sellers of used clothes. The results of the study showed: (1) The role of Customs and Excise investigators in eradicating the crime of smuggling used clothes in the Atambua City area includes preventive measures, namely socializing to the public about the smuggling of used clothes and conducting patrols. (2) The obstacles experienced by Customs and Excise investigators in eradicating the crime of smuggling used clothes in the Atambua city area include the breadth of the surveillance area, accessibility, the high interest of the Atambua community in consuming used clothes, law enforcement factors where there are still law enforcement personnel involved in smuggling, facilities or facilities where the number of transportation and investigator members is still minimal, community factors where there is still a lack of sensitivity and community participation in eradicating the smuggling of used clothes in the Atambua city area.